Phase i study evaluating the treatment of patients with hepatocellular carcinoma (HCC) with carbon ion radiotherapy: The PROMETHEUS-01 trial - Combs, Stephanie; Habermehl, Daniel; Ganten, Tom M.; Schmidt, Jan; Edler, Lutz; Burkholder, Iris; Jäkel, Oliver; Haberer, Thomas; Debus, Jürgen (BMC cancer, 2011)
Treatment options for patients with advanced hepatocellular carcinoma (HCC) are often limited. In most cases, they are not amenable to local therapies including surgery or radiofrequency ablation. The multi-kinase inhibitor sorafenib has shown to increase overall survival in this patient group for about 3 months.
Im Titel wird die Zahl eins als römische Ziffer bzw. als klein geschriebenes "i" dargestellt
Gesehen am 08.04.2022